Risk as an Indicator of Uncertainty in the Innovative Supply Chain of Enterprises - Kozlov, Anatoly; Tamer, Olga; Lapteva, Svetlana; Kruchinin, Sergey (International Journal of Supply Chain Management, 2018)
The formation of professional competence in modeling of innovative supply chain of enterprises has a number of problems associated with the instability and variability of the external environment of decision-making systems that generate uncertainty and increase the risk in decision-making. The indicator of uncertainty in such situations is the concept of "risk". This problem is especially acute in the energy sector, which not only ensures the level of peoples comfort, but is also an important component of the economy. In this regard, the importance of bachelors training is increasing. This research considers one of the ways to increase the professional training of bachelors in the oil and gas industry. To achieve this goal, a set of complementary research methods was used. The methods of analysis, generalization of theoretical and research data, and methods of mathematical modeling were most widely used. As a result, it is proposed to reorganize the course on studying risks in the innovative sphere of business. The necessary directions that will provide the maximum result for students are also indicated.